Peningkatan Kapasitas Organisasi Kepemudaan melalui Pelatihan Penyusunan Proposal di Distrik Wasior Kabupaten Teluk Wondama - Sutikno, Aldilla Yulia Wiellys; Satria Lintang Rachmadana; Sri Rizki Handayani; Rumlus, Muhammad Hasan; Muhammad Muzzaki; Faizin, Muhammad; Ernawati Simatupang; Hasny Muzdalifah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The community service program aims to increase the capacity of youth organizations (OKP) in Wasior District, Teluk Wondama Regency, through training in preparing activity proposals. Based on the observations, problems were found in preparing proposals for most OKPs, such as a mismatch between content and objectives, technical errors, and a lack of ability to use information technology. This program is implemented through several stages: planning, training, mentoring, and reporting. The training material includes using computers, preparing proposals using Microsoft Word, writing official letters, and understanding the urgency of proposals in organizations. This training improved OKP's technical and managerial capabilities, measured through monitoring and evaluation. It is also hoped that the results of this service can become a model for empowering other youth organizations, especially in remote areas.